(untitled) (Research, Society and Development, 2021)
The objective of this work was to evaluate the effects of inoculation of a strain of lactic bacteria from the digestive tract of cattle on the fermentation of elephant grass (Pennisetum purpureum cv. Cameroon). The experimental design was completely randomized with six replications of the of the following experimental groups: (CONT) Control without additive, (LACT5) Lactobacillus plantarum at Colony Forming Units per gram (CFU/g) of forage, (LACT9) L. plantarum at 1.0 × 109 CFU / g of forage. Losses of dry matter and effluent and pH after 31 days of fermentation at 37 °C were not influenced by the inclusion of the bacteria. The experimental groups did not vary their populations of lacti bacteria, yeast and mycelial fungi. However, the inoculation of this lactic bacterium reduces the population of enterobacteria and does not allow the growth of those non-fermenters of lactose. These results point to a promising potential for using this strain to reduce these pathogens in elephant grass silage.